How Gender Is Recognised in Economic and Education Policy Programmes and Initiatives: An Analysis of Nigerian State Policy Discourse - Ewoh Odoyi Ethel (MDPI, 2025)
Many African states are involved in the frontline discourse on the fight for gender equality through the adoption of public policies, aiming to improve the lives of women through social, economic, and political development. In Nigeria, despite the adoption of Article 42 of the Constitution of the Federal Republic of Nigeria 1999 adapted from the United Nations principles of gender equality, which provides for equality and elimination of all forms of discrimination against women, the Nigerian state still struggles with different forms of gendered marginalisation issues against women in various aspects of Nigerian society; these issues are mainly due to cultural, economic, and legislative challenges. Therefore, this article explores how gender is recognized through public policy programmes and initiatives using a qualitative content analysis of relevant policy documents. The documents were collected from various government ministries and cover policy areas that represent entrepreneurship and economic activities in Nigeria between 2000 and 2020. The analysis confirms the recognition of gender in public policies by subjective bias and mediating access to education for female gender advancement in Nigerian society. Some gender gaps were also recognized and discussed in the article